Development of a Survivable Cloud Multi-Robot Framework for Heterogeneous Environments. (10th October 2014) - Osunmakinde, Isaac; Vikash, Ramharuk
Cloud robotics is a paradigm that allows for robots to offload computationally intensive and data storage requirements into the cloud by providing a secure and customizable environment. The challenge for cloud robotics is the inherent problem of cloud disconnection. A major assumption made in the development of the current cloud robotics frameworks is that the connection between the cloud and the robot is always available. However, for multi-robots working in heterogeneous environments, the connection between the cloud and the robots cannot always be guaranteed. This work serves to assist with the challenge of disconnection in cloud robotics by proposing a survivable cloud multi-robotics (SCMR) framework for heterogeneous environments. The SCMR framework leverages the combination of a virtual ad hoc network formed by robot-to-robot communication and a physical cloud infrastructure formed by robot-to-cloud communications. The quality of service (QoS) on the SCMR framework was tested and validated by determining the optimal energy utilization and time of response (ToR) on drivability analysis with and without cloud connection. The design trade-off, including the result, is between the computation energy for the robot execution and the offloading energy for the cloud execution.